How consistent are Earth Observation-based machine learning models for predicting poverty in sub-Saharan Africa? - Mlambo, Reason (Jameel Observatory for Food Security Early Action, 2025)
Presented at the Jameel Observatory Community of Practice meeting and drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 13-16 May 2025